O orçamento do governo local sob condições de participação dos cidadãos: o caso da Prefeitura de Santos - Mendes, Eugenio Lima (1995)
This work deals with a case study about citizens' direct participation in the public municipal budget. It discusses the democratic theory on the basis ofthe statements that the representative democracy has flaws demanding corrective mechanisms and that the citizens' direct participation is an alternative to correct such deviations. The basic premi se of the research is that the direct partici pation is an efticient means for the citizens to control the actions of the government - Local Government. By analyzing the Party's Government Program and the Government Plan of Santos City CounciL we searched for the theoretical basis of the direct participation guiding the actions of Santos Municipal Government. The institutional dimension ofthe participation is explored through the description and criticaI analysis of the forms of direct participation in the constitutional legislation - both the Brazilian and the São Paulo State Constituition and the Organic Law of Santos City Council. We searched for identifying the limits of the mechanisms of the direct participation in the legislation as they are applied to the municipal budget. The investigation into the budget decision-making aims at finding out the logic underlying the allocation of resources in the public budget. Although there have been some legal and operational obstacles to the citizens' direct participation in the budget. such obtacles do not invalidate the importance of the experience with participatory budget in the city of Santos. Because of its innovative and educative character, Santos City Council Proposition is a valuable contribution to the practice of a more democratic and clearer municipal administration.